Improving Students’ English Speaking Skill by Using Spongebob Squarepants Cartoon - Desti Prasaja; Iis Sujarwati (International Journal of Innovation and Education Research, 2023)
According to the Indonesian curriculum, which requires students to speak, speaking is now one of the essential abilities in learning English. The four English skills that students acquire in class include speaking. Additionally, a number of problems come up throughout the teaching and learning process. Speaking difficulties frequently include anxiety while speaking in front of a group of people, a limited vocabulary and a worry about making errors. This study aims to determine whether viewing SpongeBob SquarePants with English subtitles can improve students’ speaking ability. The participants of the study consisted of 9 students from junior high school number 4 Bengkulu, enrolled in the 9th grade for the academic year 2022/2023. Purposive sampling was used to choose them for a variety of reasons. This study employed a pre-experimental methodology to investigate the impact of using the SpongeBob SquarePants cartoon on enhancing English-speaking ability. Pre-test and post-test measures are used to analyze data in this design, which does not call for a control group (Creswell & Creswell, 2018). As a consequence, employing a cartoon had a significant impact on the students’ speaking ability. It may be inferred that the research topic has been addressed and that it has been demonstrated that the application has been successful in enhancing the speaking skills of ninth-grade students. It was also found that cartoon usage application can be a center for language teacher techniques in learning English because of intense and meaningful language practice. In this study, students also do a lot of unconscious speaking skills in class because they think they are watching cartoon in a class. It shows that the students are easy to actively participate in learning that had made them used language and therefore learn it.